2019
DOI: 10.3847/1538-4357/ab2f77
|View full text |Cite
|
Sign up to set email alerts
|

Solar Models with Convective Overshoot, Solar-wind Mass Loss, and PMS Disk Accretion: Helioseismic Quantities, Li Depletion, and Neutrino Fluxes

Abstract: Helioseismic observations have revealed many properties of the Sun: the depth and the helium abundance of the convection zone, the sound-speed and the density profiles in the solar interior. Those constraints have been used to judge the stellar evolution theory. With the old solar composition (e.g., GS98), the solar standard model is in reasonable agreement with the helioseismic constraints. However, a solar model with revised composition (e.g., AGSS09) with low abundance Z of heavy elements cannot be consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 124 publications
(203 reference statements)
2
82
0
Order By: Relevance
“…We adopt a small amount of exponential convective overshooting (Herwig 2000) by choosing f ov = 0.016 as used in the MIST isochrones (Choi et al 2016). Separate implementations of convective overshooting at the base of the solar convection zone can be found in Christensen-Dalsgaard et al (2011) and Zhang et al (2019). Our calibrated solar models do not include the structural ef-fects of rotational deformation or the effects of rotational mixing.…”
Section: Solar Neutrino Luminosity Normalizationmentioning
confidence: 99%
“…We adopt a small amount of exponential convective overshooting (Herwig 2000) by choosing f ov = 0.016 as used in the MIST isochrones (Choi et al 2016). Separate implementations of convective overshooting at the base of the solar convection zone can be found in Christensen-Dalsgaard et al (2011) and Zhang et al (2019). Our calibrated solar models do not include the structural ef-fects of rotational deformation or the effects of rotational mixing.…”
Section: Solar Neutrino Luminosity Normalizationmentioning
confidence: 99%
“…Earlier theoretical studies of atomic diffusion and mixing in stellar structure calculations (Richard et al 2002;Deliyannis & Pinsonneault 1990;Proffitt & Michaud 1991;Richer et al 1992;Vauclair 1999;Chaboyer et al 2001;Richard 2005) are now being superseded by the new generation of stellar evolution models (e.g. Théado et al 2009;Vick et al 2013;Zhang et al 2019;Deal et al 2020) that include both atomic diffusion and transport processes as thermohaline convection, mass loss, rotation, or accretion. A comprehensive review of the subject can be found in Salaris & Cassisi (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Sect. 6.5 I return to this issue, based on complex modelling by Zhang et al (2019) including early accretion, mass loss and turbulent mixing.…”
Section: Abundances Of Light Elementsmentioning
confidence: 99%
“…A comprehensive effort to match observational data for the Sun, given the revised solar composition, was carried out by Zhang et al (2019), involving both pre-main-sequence accretion and early mass loss. In addition to the helioseismic data, the models were also fitted to the observed lithium abundance (see also Sect.…”
Section: Effects Of Accretion or Mass Lossmentioning
confidence: 99%
See 1 more Smart Citation